2019
DOI: 10.18621/eurj.408135
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of vertigo patients presenting to the otorhinolaryngology and neurology outpatient clinics

Abstract: Objective: Vertigo is a general term used for disorientation and is a frequent cause of admission to emergency services, otorhinolaryngology and neurology outpatient clinics. This study aims to evaluate the clinical findings, diagnostic laboratory tests, brain magnetic resonance imaging, and Doppler ultrasonography results of patients with complaints of vertigo. Methods: Patients aged >18 years who admitted to the Otorhinolaryngology and Neurology Outpatient clinics of Kahramanmaraş Sütçü İmam University Train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(21 reference statements)
0
2
1
Order By: Relevance
“…The distribution of diagnoses according to ICD-10 in this study showed that as many as 101 patients (72.93%) had peripheral vertigo, 10 patients (8.13%) had central vertigo, and the remaining 11 patients (8.94%) had dizziness. This was not much different from a previous study, where peripheral vertigo was diagnosed as much as 78.23% while central vertigo was 22.77% (8).…”
Section: Age Distributioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The distribution of diagnoses according to ICD-10 in this study showed that as many as 101 patients (72.93%) had peripheral vertigo, 10 patients (8.13%) had central vertigo, and the remaining 11 patients (8.94%) had dizziness. This was not much different from a previous study, where peripheral vertigo was diagnosed as much as 78.23% while central vertigo was 22.77% (8).…”
Section: Age Distributioncontrasting
confidence: 92%
“…81 females (65.85%) and 42 males (34.15%) (Table 1). Previous research also found that from 101 vertigo patients who were treated at OPD, 35 (31.65%) were male patients and 66 (65.35%) female patients (8).…”
Section: Age Distributionmentioning
confidence: 84%
See 1 more Smart Citation